The battle for 5Pointz and signifying regimes: desirable subjects, hierarchies of value, and legitimizing state power - Kramer, Ronald (Social semiotics, 2022)
This article offers an analysis of semiotic regimes that accompanied the redevelopment of 5Pointz and the ensuing civil lawsuits. Located in Queens, New York, 5Pointz was a building owned by GM Realty, who allowed Jonathan Cohen to curate graffiti works on its exterior and interior walls from 2002 through to 2013. I identify the ideological significance of three semiotic regimes generated by the 5Pointz saga. First, I treat "landed capital" (property development, growth machines) and "cultural commodification" (the art world) as observing systems that were central to constructing the meaning of the 5Pointz closure and litigation. These observational vantage points relied on a dichotomous logic involving desirable and undesirable subjectivity, but located key actors in distinct ways. Second, the legal outcome was often construed as a "major victory for artists." However, portraying the damages awarded as an unequivocal victory normalizes hegemonic constructions of value wherein the activities of capitalism's major players are accorded more worth than any other human activity. Finally, I focus on portraying the conflict between graffiti writers and landed capital as a "David and Goliath" battle. Signifying the conflict in such a manner (mis)construes the sovereign state as an impartial actor that adjudicates between competing rights claims.